Beyond a tokenistic inclusion of indigenous knowledge systems in protected area governance and management in Okhahlamba-Drakensberg. (15th March 2023) - Moyo, Inocent
ABSTRACT: This paper explores the perception of indigenous communities towards the co-management framework and whether or not this empowered them to utilise their indigenous knowledge systems (IKS) in the management and governance of the Protected Area (PA) in Okhahlamba-Drakensberg. IKS is excluded from the political systems of PA governance but this can be remedied through participation of indigenous communities in the agenda-setting around environmental management programmes. Indigenous community members should be co-managers at every level of the political power hierarchy of the PA if entrenched asymmetrical power relations are to be dismantled and replaced by meaningful partnership that transcends tokenistic normativity.